Mobilizing opportunities : the evolving Latino electorate and the future of American politics - Ramírez, Ricardo, 1973- (Race, ethnicity, and politics., 2013)
The growth of the Latino population is the most significant demographic shift in the United States in the early twenty-first century. Yet growth alone cannot explain this population’s increasing impact on the electorate; nor can a parsing of its subethnicities. In this significant analysis of the growing political activation of Latinos, the author identifies when and where Latino participation in the political process has come about as well as its many motivations. Using a state-centered approach, the author focuses on the interaction between demographic factors and political contexts, from long-term trends in party competition, to the resources and mobilization efforts of ethnic organizations and the Spanish-language media, to the perception of political threat as a basis for mobilization.